Organisation of the technological process of overhauling complex technical systems in the technical overhauling institution in Čačak - Radonjić, Vojkan M.; Andrejić, Marko D.; Epler, Igor J. (Vojnotehnički glasnik / Military Technical Courier, 2013)
Complex technical systems are different in comparison with other Ttechnical systems due to their complex constructions and assignments such as protection of human resources, material resources or a territory. In order that complex technical systems work correctly and have a satysfactory level of reliability and readiness, the maintenance and overhauling of such systems must take into consideration their specific technological and technical characteristics. The maintenance and overhauling of these systems must be programable and a QMS must be integrated in the maintenance and overhauling process through the whole system. The organization of complex technical systems maintenance in the Technical Overhauling Institution in Cacak for the Defence system of the Republic of Serbia is an example of such a system whose maintenance process is based on a process model of the QMS. This paper describes the maintenance and the overhauling process of Complex Technical Systems with its QMS process model which is a prerequisite for an effective and efficient maintenance and overhauling process. The overhauling process is illustrated on an example of overhauling a millitary tracked vehicle. Introduction Complex technical systems represent groups of a number of modular units (systems, subsystems, assemblies, etc..), linked as a whole with reciprocal interactions, with the aim of realizing determined functions. Complex technical systems have complex constructions and special assignments in comparison with other systems. The system of maintenance and overhauling of complex systems must be based on principles which will enable them the maximum effectiveness and efficiency in order to perform requirements given by consumers of complex systems and others subjects, with a determined level of quality of products and services, in determined time and with acceptable price. This paper describes the organisation of the process of complex systems maintenance and overhauling in the Technical Overhauling Institution, Cacak, whch deals with the highest level of system maintenance and overhauling for the defence system. It also gives the solutions based on theoretical knowledge and specific experience of the Institution and used to ensure the highest level of products and services. Conclusion The Quality Management System in the Technical Overhauling Institution improves the technological overhauling process organisation and increases the success of work in the Technical Overhauling Institution, rensposibility of the top management and all employees, the optimisation of resources consumption and it cuts down the reaction time of the Technical Overhauling Institution. The basic significance of the process of the Quality Management System in the Technical Overhauling Institution is that the bearers of work orders have a possibility to follow the course of maintenance and the realisation of work orders as well as to make decisions about work orders per operation according to the information given by all employees. The conditions are created for the maintenance and overhauling system to focus on its fundamental task – realisation of work orders within set deadlines, with the required quality of work and efficient use of resources.. Prerequisites have been created for the next step in improving the business activities of the Technical Overhauling Institution – launch of e-business